ASSISTANCE AND MAKING VCO (VIRGIN COCONUT OIL) - Usman Usman; Mastura Mastura; Hanafiah Hanafiah (Global Science Society, 2021)
The manufacture of Virgin Coconut Oil and LPPM and PM are in line with Law Number 12 of 2012 concerning Higher Education Article 45, which emphasizes that research and community service in higher education is directed at developing science and technology, as well as improving people's welfare and national competitiveness. With the VCO making program, LPPM and PM aim to avoid and fill in activities in an effort to isolate themselves, the only thing is to socialize and teach the people of Gampong Matang Neuheun, Nurussalam District, East Aceh Regency in the framework of making virgin coconut oil (VCO) as an alternative activity , so that people are not lonely and bored and traveling, and indirectly can prevent the spread of Covid-19. The service method, namely; a normative approach, empirical and using primary and secondary data, and processed descriptively qualitatively. As for the manufacturing steps; preparation of practicum tools, preparation of raw materials / old heads, splitting coconut, grating coconut, squeezing coconut into coconut milk, filtering coconut milk, depositing coconut milk in gallons of RO, , storing coconut milk in bottles / jars for 12 hours until it becomes VCO with levels 100% pure. the benefits of VCO, for health and beauty and to cure various diseases; stinging and moist as immunity naturally. The point is that in 2021, all PKM Teams will be more active and creative in the field of research and service as well as being participatory with village residents and in line with the mission of the Tridarma of Higher Education.